Pemberdayaan Masyarakat Melalui Program Edukasi dan Pemanfaatan Teknologi di Yayasan Berkah Box - Caroline Adi Cahya; Darul Ma'ruf Karim; Fatahillah Alif Arif; Indah Ayu Lumintang; Monica Anastasya Sianipar; Muhammad Alwi; Muhammad Maulana Fazri; Salfina; Khairunnisa Rahmah; Abdallah, Bayu Nur (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
This community empowerment program is a community service program that involves students to make positive contributions, creatingsynergy between universities, students, and the community in sustainable change. Students play an active role in designing andimplementing activities that empower the community and improve their quality of life, as an implementation of the spirit of service in higher education in Indonesia. The Berkah Box Mosque in North Balikpapan is a spiritual and social center that is committed to improving the quality of life of local residents through humanitarian programs. In this context, the students of the Berkah Box Mosque become human resources who are empowered to support the goals of the foundation and programs. One of the main issues is the lack of knowledge of technology and its use as an effective promotional media for branding the foundation. Effectivepromotional media is expected to increase support from donors, who are the foundation's financial source in addition to functioning asa branding tool and providing information related to the development of the foundation, the abilities of students, and other efforts tothe wider community. Through this activity, it can be achieved an increase in the participants' understanding of the various knowledge and use of technology taught in this training, namely the use of Microsoft Word, Microsoft Excel, Canva Application, Capcut, and the Creation of the Berkah Box Mosque Social Website.